Knowledge maps and their elaboration - Garzón Castrillon, Manuel Alfonso (2019)
his bibliographic review is developed through the theoretical and conceptual review of the knowledge maps and their elaboration, it is developed in the following topics: the antecedents; which is a map of knowledge; benefits of knowledge mapping; principles for the creation of the knowledge map; sources of knowledge mapping; stages for the mapping of knowledge and conclusions, Sixty-eight (68) documents were located in secondary sources of databases of scientific articles such as: Scopus, WoS, and Scielo, and the type of review is qualitative, descriptive.